ICT for food security in a changing climate: A path to women’s empowerment - Huyer, Sophia (EQUALS Research Group, 2018)
Women play a critical role in food security in the developing world, but their agricultural activities are often characterised by gaps in information and resource access, with deficiencies in several areas: land, labour, credit, information, extension and technology. Coping with the increased stresses on food security brought about by a changing climate requires the active contributions of women; their equal participation in decision making; equal access to agricultural resources and services; institutions that address their concerns; and technologies and information that are useful to them. ICT and information services have the potential to promote gender equality and empowerment of rural women if they contribute to needs and priorities of women and men in rural areas and increase their resilience to cope with climate change. However, information is not reaching women farmers adequately. ICTs are not providing them with the information, services and knowledge they need and want. Sufficient evidence and experience exists, however, to base new agricultural information strategies for food security that at the same time support women and promote gender equality. This chapter provides a review of women’s access to and use of climate and agriculture information and provides examples of successful strategies for reaching women, with suggestions for further research and programming to promote gender equality with climate information.